Cognitive inhibition impairments in presymptomatic C9orf72 carriers. Issue 4 (13th February 2020) - Montembeault, Maxime; Sayah, Sabrina; Rinaldi, Daisy; Le Toullec, Benjamin; Bertrand, Anne; Funkiewiez, Aurélie; Saracino, Dario; Camuzat, Agnès; Couratier, Philippe; Chouly, Marianne; Hannequin, Didier; Aubier-Girard, Carole; et al.
Abstract : Objective: To investigate cognitive inhibition in presymptomatic C9orf72 mutation carriers (C9+) and its associated neuroanatomical correlates. Methods: Thirty-eight presymptomatic C9orf72 mutation carriers (C9+, mean age 38.2±8.0 years) and 22 C9− controls from the PREV-DEMALS cohort were included in this study. They underwent a cognitive inhibition assessment with the Hayling Sentence Completion Test (HSCT; time to completion (part B−part A); error score in part B) as well as a 3D MRI. Results: C9+ individuals younger than 40 years had higher error scores (part B) but equivalent HSCT time to completion (part B−part A) compared to C9− individuals. C9+ individuals older than 40 years had both higher error scores and longer time to completion. HSCT time to completion significantly predicted the proximity to estimated clinical conversion from presymptomatic to symptomatic phase in C9+ individuals (based on the average age at onset of affected relatives in the family). Anatomically, we found that HSCT time to completion was associated with the integrity of the cerebellum. Conclusion: The HSCT represents a good marker of cognitive inhibition impairments in C9+ and of proximity to clinical conversion. This study also highlights the key role of the cerebellum in cognitive inhibition.